ROBOT PENDETEKSI DAN PENGHITUNG JALAN BERLOBANG MENGGUNAKAN SENSOR INFRA MERAH BERBASIS MIKROKONTROLER AT89S51 - Prama Wira Ginta; Raden Fenni Milati (Jurnal Media Infotama, 2011)
Robot Detection And Counters Road perforated Using Infrared Sensor-Based Microcontroller AT89S51 is a robot designed to follow the line and is equipped with infrared sensors as detection aperture, alarm indicator as there are holes, and counter up as a counter aperture of the detection results, and comes with applications using Visual Basic 6.0 as counte up on the computer. In this research tool has been designed in the form of hollow road robot detection and application of robots counter counter up hollow road detection. From the test results and application of robots, robotic and computing dikethui hollow road detection and application of robot detection counter up the road can be perforated to function properly, the robot can calculate and detect holes, and the application can calculate the detection of hollow road detection using infrared sensors .